Models of Backwardness versus Transformation in Eastern Europe. Review Article - Brzechczyn, Krzysztof (The University of Colorado, 2008)
This paper is critical analysis of book by Anna Sosnowska, "Zrozumieć zacofanie. Spory historyków o Europę Wschodnią (1947-1994)" [To Understand Backwardness: Historians' Deabates about Eastern Europe (1947-1994)]. Warszawa 2004.
Keywords: backwardness; Eastern Europe; history of historiography; transformation